"May You Be the Mother of A Hundred Sons!": Barrenness vs. Motherhood in Bengali Cinema. Issue 1 (1st March 2011) - Mandal, Somdatta
Beginning with barrenness as the root cause in the break-up of husband-wife relationships in several films of Satyajit Ray namely Monihara, Devi, Charulata and Ghare-Baire, Somdatta Mandal also examines Punendu Patrea's Streer Patra, Rituparno Ghosh's Chokher Bali and Antarmahal (The Inner Chamber) where the director narrates a 19th century tale of a Bengali zamindar whose desperation in begetting a male heir leads to bizarre circumstances. But first with Satyajit Ray's handling of the theme. Among the different forms of portraiture of women in the films of Satyajit Ray, the married and childless wife reveals herself in different avatars. In most cases, these women become sort of loners, or outcasts, bereft of normal heterosexual behavior. It is more than a coincidence in each case that the woman protagonist turns out to be childless.